2021
DOI: 10.3389/fendo.2021.718429
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic Signaling in Liver Pathophysiology

Abstract: Extracellular nucleosides and nucleotides activate a group of G protein-coupled receptors (GPCRs) known as purinergic receptors, comprising adenosine and P2Y receptors. Furthermore, purinergic P2X ion channels are activated by ATP. These receptors are expressed in liver resident cells and play a critical role in maintaining liver function. In the normal physiology, these receptors regulate hepatic metabolic processes such as insulin responsiveness, glycogen and lipid metabolism, and bile secretion. In disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 106 publications
0
18
0
1
Order By: Relevance
“…Even circulating adenosine and nucleotides may stimulate hepatic glycogenolysis [ 41 ]. This may involve purinergic signaling via G-protein-coupled receptors (GPCRs) activated by adenosine or nucleotides [ 42 , 43 , 44 , 45 ]. Speculatively, endocannabinoids might also influence hepatic glucose metabolism via GPCRs [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Even circulating adenosine and nucleotides may stimulate hepatic glycogenolysis [ 41 ]. This may involve purinergic signaling via G-protein-coupled receptors (GPCRs) activated by adenosine or nucleotides [ 42 , 43 , 44 , 45 ]. Speculatively, endocannabinoids might also influence hepatic glucose metabolism via GPCRs [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Purinergic receptor family molecules mainly include 7 members, which are widely involved in many biological processes, such as energy metabolism, inflammatory response, and cell proliferation [14][15][16] . A large number of studies have confirmed that ATP-mediated purine signals play an important role in cancer progression and immune regulation [17][18][19][20] . As a member of P2X receptor family, P2RX1 is involved in mediating synaptic transmission between neurons or smooth muscle, arterial vasoconstriction, reproductive regulation, apoptosis, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine is a ubiquitous nucleotide metabolite that rapidly increases within the extracellular space in several stress and distress conditions, modulating tissue function and damage [11,12]. The liver is centrally involved in nucleotide production and metabolism, and increasing evidence shows that nucleotide metabolites have a main role in modulating liver health and disease [13,14]. Adenosine, in fact, both regulates physiological liver processes like carbohydrate and lipid metabolism and acts as a damaging or protective agent, promoting or preventing different hepatic pathologies such as fibrosis, steatohepatitis, carcinogenesis and ischemia-reperfusion injury [14].…”
Section: Introductionmentioning
confidence: 99%
“…Adenosine is signaled by activating the four G-coupled adenosine receptors (ARs): A1AR, A2AAR, A2BAR and A3A [11,12,15]. All ARs are expressed in the liver [13,14] and among them, A1AR and A2AAR display the highest affinity for adenosine [11,13].…”
Section: Introductionmentioning
confidence: 99%